2016
DOI: 10.1371/journal.pone.0156738
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing Reveals Novel Genetic Variants in Children with Acute Liver Failure and Tissue Evidence of Impaired Energy Metabolism

Abstract: Background & AimsThe etiology of acute liver failure (ALF) remains elusive in almost half of affected children. We hypothesized that inherited mitochondrial and fatty acid oxidation disorders were occult etiological factors in patients with idiopathic ALF and impaired energy metabolism.MethodsTwelve patients with elevated blood molar lactate/pyruvate ratio and indeterminate etiology were selected from a retrospective cohort of 74 subjects with ALF because their fixed and frozen liver samples were available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Seven patients were reported by Bourdon et al, 2 but they included one patient, which has been reported earlier by Paqulis-Flucklinger et al 3 why only six of these patients were evaluated for phenotype analysis. Three patients were reported by Bornstein et al 4 Two patients each were reported by Kropach et al, 1 Pitceathly et al, 13 Spinazzola et al, 5 Kollberg et al, 6 and Valencia et al 12 One patient each was reported by Paqulis-Flucklinger et al, 3 Acham-Roschitz et al, 7 Stojanovic et al, 8 Hernández-Laín et al, 9 Shaibani et al, 11 Takata et al, 15 and by Wilichowksi et al 16 A single patient carrying a RRM2B variant was also reported by Horga et al 18 However, this case was excluded since no individual data were reported and since the case could have been included in the paper by Pitceathly et al 10 already. The paper by Wilichowski et al 16 was published only as an abstract so far (►Table 1).…”
Section: Number Of Publications and Patientsmentioning
confidence: 98%
See 3 more Smart Citations
“…Seven patients were reported by Bourdon et al, 2 but they included one patient, which has been reported earlier by Paqulis-Flucklinger et al 3 why only six of these patients were evaluated for phenotype analysis. Three patients were reported by Bornstein et al 4 Two patients each were reported by Kropach et al, 1 Pitceathly et al, 13 Spinazzola et al, 5 Kollberg et al, 6 and Valencia et al 12 One patient each was reported by Paqulis-Flucklinger et al, 3 Acham-Roschitz et al, 7 Stojanovic et al, 8 Hernández-Laín et al, 9 Shaibani et al, 11 Takata et al, 15 and by Wilichowksi et al 16 A single patient carrying a RRM2B variant was also reported by Horga et al 18 However, this case was excluded since no individual data were reported and since the case could have been included in the paper by Pitceathly et al 10 already. The paper by Wilichowski et al 16 was published only as an abstract so far (►Table 1).…”
Section: Number Of Publications and Patientsmentioning
confidence: 98%
“…RRM2B mutations have been reported in 82 patients in 18 publications so far (►Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The largest number of patients (n ¼ 26) was reported in a paper by Pitceathly et al 10 but 11 of these patients were described as having been reported earlier, without detailing the particular publications in which these 10 patients have been mentioned (►Table 1). 10 Seventeen patients carrying a RRM2B mutation from two families were reported by Tyynismaa et al 2009.…”
Section: Number Of Publications and Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to drug‐specific factors, susceptibility to DILI varies by patient. For example, children with mitochondrial polymorphisms/disorders are highly susceptible to drug‐induced acute liver failure and fatality . Furthermore, drug metabolism and immune response are influenced by concomitant medications, inflammation, and genetics .…”
Section: Personal and Environmental Risk Factors Affect Liver Injurymentioning
confidence: 99%